Justice involvement among homeless individuals with mental illnesses: Are self-report and administrative measures comparable?. (April 2017) - Lemieux, Ashley J.; Roy, Laurence; Martin, Michael S.; Latimer, Eric A.; Crocker, Anne G.
Highlights: Individuals who are homeless and diagnosed with mental illness have high rates of justice involvement. Agreement between self-reported and official justice involvement is generally good. Sociodemographic characteristics, psychiatric diagnosis, criminal history, substance related disorders, and interviewers impressions are predictive of discrepant reporting. Level of agreement and predictors of discrepant reporting are similar across type of outcome (dichotomous, categorical, or discrete). Strategies for optimizing follow-up may increase reliability of self-reports through interviewer-participant rapport. Abstract: Individuals with mental illnesses who experience homelessness have frequent interactions with the criminal justice system. Correctly measuring this involvement is essential to develop and evaluate the efficacy of intervention programs. Criminal justice involvement is typically assessed through administrative records or self-reported accounts. The aims of this study are to: 1) assess agreement between self-report and administrative data related to court appearances, and 2) identify individual characteristics that affect discrepancies between sources. Participants were 468 homeless persons with mental illness from the Montreal site of the At Home/ Chez Soi randomized controlled trial, in Canada. Self-reported data was collected through an interviewer-administered questionnaire. Administrative data was collected through provincial and municipal court databases. Overall, agreement was good. Discrepancies were more common among those with a diagnosis of mood disorder with psychotic features, and those with a criminal history. Increased age and interviewer's perception of sincerity and interest increased likelihood of concordance. Generally, high agreement between self-report and administrative data suggests that either source can provide reliable information. Further work to understand predictors of discrepancies could further enhance the quality of data collected through these different sources.